Karakteristik dan Distribusi Spasial Bahan Organik Pada Sedimen Dasar Perairan Teluk Pacitan Jawa Timur - Dewi, Alindya Eka Puspita; Hidayah, Zainul; Farid, Akhmad; Wiyanto, Dwi Budi (Journal of Marine and Aquatic Sciences, 2022)
Pacitan Bay is one of the semi-enclosed waters on East Java's south coast. This area is well-known for having a large fishing port as well as a beach tourism area. The dynamics of Pacitan Bay's waters due to the influence of currents, waves, and the input of water masses from the mainland are thought to affect the characteristics of the waters' bottom sediments. The objective of this study was to map the characteristics of bottom sediments and the distribution of organic substance. This research also analyzed the relationship between sediment characteristics and the concentration of organic subtance in the sediment. The sediment's characteristics were determined using granulometric analysis, and the organic matter content was determined using the Loss of Ignition (LOI) method. The analysis results show that sandy substrates dominate the bottom sediments of Pacitan Bay by an average of 82.22%. The distribution of sandy substrate dominates the bay's north and west. Distance from the shoreline has a significant effect on organic subtance distribution (One Way ANOVA, F = 6.05; p 0.05). The organic matter content of sediments dominated by sand is lower (R2 = 0.76) compared to substrates with softer grain size (silt or mud) and tighter pores, making organic matter efficient to precipitate.